Amplifying a Relational Ethic: A Contribution to PRME Praxis. (March 2015) - Verbos, Amy Klemm; Humphries, Maria
Abstract Western economically driven instrumental ethics fuel the dominant institutional logic in many business schools and are associated with the negative social and environmental situation widely linked to the mode of global development. Other ethical framings have been subordinated, marginalized, or denied. Through the explicit commitment of prominent international certifying bodies of management education, educators, researchers, and practitioners will be encouraged to give increasing effect to the Principles for Responsible Management Education (PRME). The PRME is a United Nations‐led, institution‐level mechanism for reorienting the direction of business schools and for increasing both educator and student capacities to contribute to a more inclusive and sustainable mode of development globally. We propose greater emphasis be given to various forms of relational ethics from which to guide the functional aspirations of institutions. We explore the creative opportunity for institutional change by contrasting the prevailing Western economically driven instrumental institutional logic with indigenous ethical framings. We draw upon Seo and Creed's conceptual framework of institutional change to discuss two films—Mann v. Ford and Waste = Food—to bring greater attention to the generative potential of indigenous perspectives in institutional praxis. Our examples could equally invite an application of other systems of relational ethics that have been overshadowed by the current domination of economic instrumentalism in almost all realms of decision making. We conclude by providing some teaching resources that can be used or adapted for geographical‐ or disciplinary‐specific attention to the issues we raise.